Planning and distribution of primary educational services: Trinidad and Tobago - (Mission) 10-21 March 1975 - Chesswas, John
This report on school distribution in Trinidad and Tobago, with particular reference to primary schools and educational resources, discusses and considers the following: 1) factors of educational policy relating to private schools, compulsory education, and the entrance examination to secondary education; 2) the relationship between enrolment projections of the school-age population, regional planning, and human settlements; 3) statistical methodology for educational statistics; 4) educational planning for the development of primary education; and 5) projections for primary school teachers and for educational financing\
Keywords: School mapping